To Stabilize Shear Strength Properties of an Unwanted Subgrade Soil Utilizing Rock Dust - Qaim Shah; Kwabene Byemba; Garzali Gali; Ali Muhammad; Adnan Khan; Murad Khan (Journal of ICT, Design, Engineering and Technological Science, 2023)
When a pavement fails, the subgrade is displaced laterally due to the pavement absorbing water, excessive deflection, and differential settling of the material beneath the pavement. The purpose of the study is to determine how rock dust additions affect the stability and increased bearing capacity of certain soils in Mardan City. For the objective of stabilizing the native soil, the physical, chemical, and engineering qualities of the soil were investigated. The soils were then treated with additions (rock dust). Rock dust is added to soils with a percentage increase of 5%, 10%, and 15%, respectively, to stabilize soils from 0 to 85%. Atterberg limits (liquid limit, plasticity index, and plastic limit), Specific Gravity, gradations test, and direct shear test were performed on the treated sample. The exact temperature and moisture content for maturation were applied to all samples. The results of the particle size study indicated that the soil's gradation is thin. With the addition of rock dust, the plasticity index (P.I.), liquid limit (L.L.), and plastic limit (P.L.) were all reduced. With the addition of rock dust, it was discovered that the value of cohesion c reduced, and the angle of internal friction decreased. The Research revealed that rock dust, at an ideal concentration of 10%, is the best stabilizer for the case study (Toru Road, Mardan City).